A low-cost portable simulator of a domestic cat larynx for teaching endotracheal intubation - Clausse, María (2020)
Objective: To design and construct an affordable simulator of the cat larynx for training intubation maneuvers and to share the designs for its fabrication. Study design: Research and development study. Animals: A domestic cat. Methods: The cadaver of a cat, dead by natural causes, was frozen in sternal recumbency with the neck extended and the mouth wide open. A computed tomography image was acquired and used to construct a digital three-dimensional (3D) model of the pharynx and trachea. A digitally adapted model was 3D-printed and used to generate a silicone model of these structures, which was placed within a wooden container. The quality of the simulator was assessed by 46 veterinary anesthesiologists and veterinarians with experience in tracheal intubation maneuvers, and their opinions were obtained through an anonymous questionnaire. Results: Several preliminary prototypes were assessed regarding stability, texture and cost. Finally, a silicone model of a cat larynx (LaryngoCUBE) was produced and encased in a wooden container. Results from the questionnaire showed high scores regarding anatomy, tissue texture and intubation maneuver realism, compared with the real procedure. Conclusions: and clinical relevance Use of LaryngoCUBE as a training tool may improve the skills of students and reduce the use of animals for teaching endotracheal intubation. Blueprints and computational models are provided online so that the simulator can be fully reproduced.